COMPARISON OF CARDIOVASCULAR SAFETY OF BUPIVACAINE AND ROPIVACAINE ADMINISTERED BY SUPRACLAVICULAR BLOCK IN PATIENTS UNDERGOING UPPER ARM SURGERY: Pharmaceutical Science-Toxicology - PRAMOD HARISHCHANDRA KATKE; MIRZA SHIRAZ BAIG; PRAVEEN HARISHCHANDRA KATKE (International Journal of Life Science and Pharma Research, 2022)
Bupivacaine and Ropivacaine were widely used long acting local anesthetic agents in regional anesthesia. Though efficacious, cardiovascular adverse drug reactions are known safety concerns with use of long acting local anesthetic agents, especially with Bupivacaine. The aim of this study was to compare the cardiovascular safety of Bupivacaine and Ropivacaine in patients receiving supraclavicular brachial plexus block for upper arm surgery. It was a randomized, double blind, controlled, prospective study. Screened patients fulfilling the inclusion and exclusion criteria were randomized to receive supraclavicular block using nerve locator with 40 ml of either Bupivacaine 0.5% or Ropivacaine 0.5%. Parameters under study such as pulse rate, blood pressure, electrocardiogram recordings such as PR interval, QRS duration and QT interval were compared from the start of the study to regular intervals such as during the study, post operatively and at follow up using paired T test and intergroup comparison were made using unpaired T test. It was observed that the pulse rate, blood pressure, PR interval, QRS duration and QT interval didn‟t differ significantly from the baseline when compared to various intervals such as during surgery, post operatively and at follow up (p value>0.05). There was no significant difference between the pulse rate, blood pressure, PR interval, QRS duration and QT interval on intergroup comparison (p value > 0.05). In the present study, both the local anesthetic agents Bupivacaine and Ropivacaine did not produce any cardiovascular changes in patients receiving supraclavicular block using nerve locator.